El régimen de supervisión, inspección y sanción del Banco de España en la Ley 10/2014 - Carmen Chinchilla Marín (Revista Vasca de Administración Pública, 2015)
This study deals with the powers of supervision, inspection and sanction of the Bank of Spain in the light of Act 10/2014 of management, supervision and solvency of the credit institutions. This works deals also with another «institutions», differents to credit ones, which are also subjected to the supervision of the Bank of Spain. Additionally, it takes into account of the novelty of the shared exercise among the Bank of Spain and the European Central Bank of some powers regarding credit institutions as a consequence of the establishment and coming into force of the Single Supervisory Mechanism (SSM). This work does not tackle the issue of the faculties of the Bank of Spain as a authority for the preventive resolution since its regulation is addressed by a different Act ¿the recently enacted Act 11/2015 from June 18th of recovery and resolution of credit institutions and investment firms, derogating Act 9/2012¿ which deserves further study. Nevertheless, the changes operated upon the LOSSEC are studied together with the novelties introduced regarding the issues dealt with in this work.